Vocational Education as Empowerment Motivation for The Skills of Sorong Special School Students - Veronika, Penni; Dian Nitari Ribanor Sabarudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research uses qualitative research, with a phenomenological model where this research aims to determine the role of motivation and empowerment in Sorong special schools. The focus of this research is students and teachers using a purposive sampling method, using data analysis techniques from interviews with 6 principals and teachers, interviews with 10 students, as well as the results of observations of disability skills classes at the Sorong special school. Research data was obtained through semi-structured interviews assisted by a documentation process related to the entire learning process of students with disabilities related to skills. This research uses data reduction analysis techniques, data presentation, and drawing final conclusions. Research data shows that all school structures play an active role in developing the skills of students with disabilities